Guttate psoriasis: a case of unusual evolution of an occupation-related skin chemical burns - Schicchi, Azzurra; Tresoldi, Marco M; Petrolini, Valeria M; Lonati, Davide; Perrone, Maria; Locatelli, Carlo A (La Medicina del Lavoro, 2021)
Introduction: Chemical burns are a risk in domestic and occupational accidents due to the common use of caustic agents. Long-term sequelae are normally due to the amount of skin and underlying tissues damaged. We describe a case of work-related chemical burns with unusual evolution in guttate psoriasis. Case Report: A 36 years-old man was admitted to the Emergency Department (ED) three-hours after a work accident. During the cleaning of an industrial hydraulic system, a jet of hydrochloric acid 20% injured his face and upper limbs. At ED admission, he presented first and second-degree skin burns on the frontal region, on the scalp, on the right forearm, and earlobe. Plastic surgery management consisted in wound topical dressing with silver sulfadiazine and paraffin gauze twice a week for one month. Forty-eight hours after the latter topical treatment (45-days after the work accident), in the same anatomical regions of the previous burn scars, he developed a skin reaction with itchy erythema. The application of topical products was suspended without improvement, excluding an allergic reaction. Within few days, a generalized guttate psoriasis was evident on the whole body. Discussion: Despite many prevention actions, work-related burns are a relatively common cause of hospitalization and may involve up to 80% of patients admitted to a burn unit. Guttate psoriasis has not been described as a sequelae of chemical burns. In our case, the others most frequent factors causing guttate psoriasis have been ruled out. Considering the temporal link between the development of guttate psoriasis and the work accident, hydrochloric acid skin burns might have promoted the systemic inflammatory mediators’ mechanism involved in the development of guttate psoriasis lesion’s after the dermal injury.